Early Detection Efforts by the Intelkam Unit in Conflict Prevention Between Silat Colleges in the Jurisdiction of Nganjuk Police (Advances in Police Science Research Journal, 2024)
This research aims to analyze the efforts of the Police Intelligence Unit (Satintelkam) in preventing conflicts between silat schools in the jurisdiction of the Police Nganjuk. Through data collection techniques such as interviews, observations, and studies document, the author highlights the steps that Satintelkam has taken, such as gathering information, investigations, and collaboration with institutions related. However, there are several obstacles faced, such as limitations number of personnel, development education that is not yet optimal, and limitations tools for closed investigations. Based on these findings, the author recommend the use of information technology, additional personnel, increasing development education, and increasing the budget for alsus intelligence as steps to increase the effectiveness of Satintelkam efforts in preventing conflicts between martial arts schools in the region.
Keywords: DETEKSI DINI; PERGURUAN SILAT; KONFLIK; SATINTELKAM